Leagile supply chains and sustainable business performance: application of total interpretive structural modelling - Mohaghegh, Matin; Größler, Andreas (Production planning & control, 2025)
This study aims to develop an integrated model for the leagile (lean + agile) supply chain strategy to achieve sustainable business performance across the triple bottom line, including economic, environmental, and social performance. We draw upon a literature review and experts' opinion, using total interpretive structural modelling (TISM), to determine interrelationships among leagile supply chain practices and sustainable business performance measures. To this end, first, unique and common practices of lean and agile supply chain strategies, i.e. leagile building blocks, are identified through a synthesis of the literature. Second, semi-structured interviews with four experts are conducted to gain an understanding of the mutual relationships among the leagile building blocks and to meticulously adjudicate their interactions with sustainable business performance measures. Validated by two independent researchers and literature enfolding, the final TISM model provides a 10-level hierarchical representation of the leagile supply chain strategy for sustainable business performance.